Dismantling Rape Culture: The Need for a Comprehensive Educational Approach - Halsne, Chase (2019)
The perpetuation of rape culture is a central issue for feminist theory. In this paper, I argue for a comprehensive educational approach for undermining rape culture. I begin by outlining the reliance of rape culture on problematic social norms, particularly dominant conceptions of sexuality. I then briefly sketch a comprehensive educational approach and its advantages. Included in this sketch are critiques of two other feminist strategies for undermining rape culture: feminist legal reform and feminist self-defense training. I conclude by considering possible objections and attempt to provide solutions to foreseeable problems with my approach